2012
DOI: 10.1007/978-1-62703-002-1_2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Nanomaterials for Toxicological Studies

Abstract: The scientific community, regulatory agencies, environmentalists, and most industry representatives all agree that more effort is required to ensure the responsible and safe development of new nanotechnologies. Characterizing nanomaterials is a key aspect in this effort. There is no universally agreed upon minimum set of characteristics although certain common properties are included in most recommendations. Therefore, characterization becomes more like a puzzle put together with various measurements rather th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Far than chemical composition, size and shape are crucial factors determining the relationships between nanoparticles and increasingly complex biological systems (namely from cells to entire organisms) in critical aspects such as organ specificity and biodistribution [36][37][38][39][40], toxicity [41], and cell uptake and fate [39,[42][43][44][45]. Although previously checked in several types of nanostructures, mainly in crystalline nano-and micromaterials, the present study is the first evaluation of form (geometry) and function (cellular uptake) of protein nanoparticle populations.…”
Section: Discussionmentioning
confidence: 99%
“…Far than chemical composition, size and shape are crucial factors determining the relationships between nanoparticles and increasingly complex biological systems (namely from cells to entire organisms) in critical aspects such as organ specificity and biodistribution [36][37][38][39][40], toxicity [41], and cell uptake and fate [39,[42][43][44][45]. Although previously checked in several types of nanostructures, mainly in crystalline nano-and micromaterials, the present study is the first evaluation of form (geometry) and function (cellular uptake) of protein nanoparticle populations.…”
Section: Discussionmentioning
confidence: 99%
“…Since a complete and exact list of parameters influencing the toxicity of ENMs has not been established yet, a detailed material characterization prior to toxicity testing is essential to determine the factors contributing to the biological activities of ENMs and their potential hazards. Although there is still no scientific consensus on the minimum set of relevant nano-characteristics for toxicological evaluation, some particular physicochemical features are repeatedly emphasized in the majority of recommendations (Kevin W Powers, Carpinone, & Siebein, 2012). The size of ENMs is one of the most prominent key characteristics which is held responsible for the changing properties and behaviour of ENMs and hence included in the recommendation list of almost all nanotoxicologists.…”
Section: Possible Factors Affecting the Toxicity Of Enms And Their Mementioning
confidence: 99%
“…The following characteristics may also be linked to nanotoxicity: size distribution, agglomeration state, shape, crystal structure, chemical composition, surface area, surface chemistry, surface charge and porosity. (Kevin W Powers, et al, 2012) have investigated the key elements of NM characterization and expanded the list provided by (Oberdorster, et al, 2005) to include purity, solubility and hydrophobicity. In the recent review on the minimum set of physicochemical properties needed to characterize NMs, (Pettitt & Lead, 2013) have suggested that in addition to the parameters that are most likely to have an effect on NM behaviour such as size, surface properties, solubility and aggregation characteristics, information about the production process and history of ENMs should also be provided to avoid incorrect interpretation of toxicity data.…”
Section: Possible Factors Affecting the Toxicity Of Enms And Their Mementioning
confidence: 99%
See 1 more Smart Citation
“…The use of nanoparticles (NPs) has steadily increased over the past decade, due to their unique physical and chemical properties ( 1 , 2 ) and has raised growing concern about their possible effects on human health ( 3 ). Given the small size and biocompatibility, NPs are potentially able to enter the body through different routes, such as inhalation, ingestion, skin uptake, injection, or implantation and interfere with several cellular physiological processes ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%